Dynamic response of three dimension tunnel on elastic foundation subjected to moving vehicle loads - Chung, Nguyen Thai; Tien, Do Ngoc (Vietnam Journal of Mechanics, 2015)
Dynamic response analysis of tunnel with elastic foundation subjected to the load such as the hydrostatic pressure, seismic or moving load is an important but complicate problem in transport engineering due to increasing of traffic volume. This paper is devoted to study dynamic response of a tunnel surrounded by elastic foundation under moving vehicle loads by using the finite element method (FEM). The numerical results were then validated by an experimentation on a real structure.